Evaluation of Drug Use at Pasar Merah Public Health Center in Medan - Ismedsyah Ismedsyah; Takarina Takarina (Journal of Pharmaceutical and Health Research, 2021)
Evaluation of drug use is one of the clinical pharmacy services at Public Health Center. Evaluation of the drugs use must refer to the indicators of drug use.This study aimed to determine the average number of drugs in each prescription, the percentage of prescribed generic drugs, the percentage of prescribed antibiotics, the percentage of injection, and the percentage of drugs prescribed from the DOEN (List of National Essential Medicines) at Pasar Merah Public Health Center Medan. This research was a retrospective descriptive study carried out by collecting data from the available documents as well as interviews with the head of Medan Pasar Merah Public Health Center and drug management officers.Through the research, it was found that the average number of drugs in each prescription was still high, not in accordance with the prescribed standards, the percentage of generic drugs prescribed was not good, the percentage of prescribed antibiotics was quite high, the percentage of injections prescribed did not meet the percentage indicator of injection prescription, and the percentage of drugs prescribed from the DOEN at Pasar Merah Medan Public Health Center was quite good. This study concludes that the use of drugs in Pasar Merah Medan Public Health Center has not met the indicator of drug use